An Extension of Particle Swarm Optimization (E-PSO) Algorithm for Solving Economic Dispatch Problem - Zakaria, Zetty N.; Azmi, Azralmukmin; Laili, Muhammad S.; Syed Jamalil, Syed A.; Sulaiman, Mohd H. (AIMS 2013 : proceedings : first International Conference on Artificial Intelligence, Modelling & Simulation : 3-5 December 2013, Kota Kinabalu, Sabah, Malaysia, 2013)
Producing the energy power that meets the load demands at a minimum cost while satisfying the constraints is known as economic dispatch. Economic dispatch becomes one of the most complex problems in the planning and operation of a power system that aims to determine the optimal generation scheduling at minimum cost. For that reason many optimization researches on finding an optimal solution regarding the total cost of generation have been carried out. This paper presents the implementation of the extension of the PSO (E-PSO) system in solving the continuous nonlinear function of the cost curves of the generator. In this paper, a 6-unit generation system has been applied to show the effectiveness of the E-PSO compared to the standard PSO. The results show that E-PSO is capable in solving the economic dispatch problem in term of minimizing the total cost of generation while considering the generator limits and transmission losses.